1372. Comparison of Healthcare Resource Utilization (HRU) Among Adult Patients Treated with Omadacycline (OMC) for Acute Bacterial Skin and Skin Structure Infections (ABSSSI) or Community-Acquired Bacterial Pneumonia (CABP) in the 30 Day Pre- and Post-OMC Prescription (Rx). (4th December 2021) - Lodise, Thomas; Lodise, Thomas; Gunter, Kyle; Rodriguez, Mauricio; Miu, Fan; Gao, Emily; Yang, Danni; Sandor, Steve; Berman, Gail
Abstract: Background: Assess 30-day real-world outcomes associated with OMC for the treatment of adults with ABSSSI or CABP. Thirty-day outcomes are an important quality metric for both private and public payers. This retrospective study compared HRU among adult pts treated with OMC for ABSSSI or CABP in the 30-day pre- and post-OMC Rx periods. The pre-post study design was selected to assess how 30-day HRU changed post-OMC RX (proxy for treatment response). Methods: Pts who received ≥1 OMC outpatient Rx from a large US claims database (10/2018-9/2020) were identified. Pts were classified as ABSSSI or CABP cohort based on presence of ICD-10 code near (-90 d to +30 d) OMC Rx. Within each diagnosis, pts were classified as complicated if any of the following infections were identified in the pre-period (-90 d to + 5 d) (ABSSSI: osteomyelitis (OST), sepsis/bacteremia (S/B), endocarditis, implant, necrotizing fasciitis, meningitis; CABP: severe pneumonia, lung abscess, S/B, endocarditis, meningitis). Risk of inpatient admissions (IP), ED visits, outpatient visits (OP) were compared between the following 2 periods: 30 days pre- and 30-days post-OMC Rx. Results: During study period, 258 OMC outpatient Rx met inclusion criteria: 189 were ABSSSI and 69 were CABP. Among the 189 ABSSSI pts, 83 were complicated. Most common ABSSSI complicated were OST (53%), S/B (33%), and implant infection (21%). Among the 69 CABP pts, 20 were COM. Most common CABP complicated were S/B (80%) and severe pneumonia (25%). Comparison of HRU in the 30 days pre- to the 30-day post-OMC Rx period are shown in Tables 1 and 2. Among complicated ABSSSI pts, IP decreased by 38% (41% vs 25%; p< 0.05) while ED visits and OP were similar. Among non- complicated ABSSSI pts, IP decreased by 61% (17% vs 7%; p< 0.05), ED visits decreased by 88% (16% vs 2%; p< 0.01) while OP were similar. Among complicated CABP pts, IP decreased by 75% (80% vs 20%; p< 0.01), ED decreased by 100% (40% vs 0%; p< 0.001) while OP were similar. Among non- complicated CABP pts, IP decreased by 75% (33% vs 8%; p< 0.01), while ED visits and OP were similar. Table 1. Comparison of HRU in the 30-day pre-OMC Rx vs 30-day post-OMC Rx period among ABSSSI pts Table 2. Comparison of HRU in the 30-day pre-OMC Rx vs 30-day post-OMC Rx period among CABP pts Conclusion: This study provided the first real world characterization of pts treated with OMC for ABSSSI or CABP. Patients who received OMC had lower HRU in the 30-days post- OMC Rx period relative to the 30-day pre-OMC Rx period. Disclosures: Thomas Lodise, Jr., PharmD, PhD, Astra-Zeneca (Consultant)Bayer (Consultant)DoseMe (Consultant, Advisor or Review Panel member)ferring (Consultant)genentech (Consultant)GSK (Consultant)Melinta (Consultant)merck (Consultant, Independent Contractor)nabriva (Consultant)paratek (Consultant, Advisor or Review Panel member, Speaker's Bureau)shionogi (Consultant, Advisor or Review Panel member, Speaker's Bureau)Spero (Consultant)tetraphase (Consultant)Venatrox (Consultant) Thomas Lodise, Jr., PharmD, PhD, Melinta Therapeutics (Individual(s) Involved: Self): Consultant; Merck (Individual(s) Involved: Self): Consultant, Scientific Research Study Investigator; Paratek (Individual(s) Involved: Self): Consultant; Shionogi (Individual(s) Involved: Self): Consultant, Speakers' bureau; Spero (Individual(s) Involved: Self): Consultant; Tetraphase Pharmaceuticals Inc. (Individual(s) Involved: Self): Consultant Kyle Gunter, PharmD, MBA, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Mauricio Rodriguez, Jr., PharmD, BCPS, BCCCP, BCIDP, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Fan Miu, PhD, Analysis Group (Employee, Other Financial or Material Support, Analysis Group received consulting fees from Paratek Pharmaceuticals, Inc.) Emily Gao, MS, MPH, Merck & Co., Inc. (Consultant) Danni Yang, BA, Analysis Group (Employee, Other Financial or Material Support, Analysis Group received consulting fees from Paratek Pharmaceuticals, Inc.) Steve Sandor, JD, MBA, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Gail Berman, MD, Paratek Pharmaceuticals, Inc. (Employee, Shareholder)